Pelatihan Membuat dan Mengelola Web Blog sebagai Media Pembelajaran yang Efektif untuk Guru-guru SMP Se-Kecamatan Tanjung Batu Ogan Ilir - Megah Mulya; Al Farissi; Osvari Arsalan (Annual Research Seminar (ARS), 2016)
This paper contains the reports of training activities to create and manage web blog as a medium of instruction for effective teachers throughout the Tanjung Batu district implemented in SMP Negeri 2 Tanjung Batu. In the Tanjung Batu district, the teachers are still many who have not use web blog as a medium of learning even still there are teachers who have not been able to use the computer. On the other side of the school should implement kurikulum 2013 which requires applying computer-based learning. This training of 22 participants resulting from all able to switch on and off the computer correctly, all able to use the windows operating system are limited, 91% were able to create and utilize email, and 77% are able to create and manage web blog.